Vascular restenosis in coronary artery bypass grafting might be associated with VEGF-C/VEGFR-3 signaling pathway - Podemska-Jedrzejczak, Zuzanna (Heart Vessels, 2018)
The vascular endothelial growth factor (VEGF) family of peptides and caveolins (CAVs) are reported to contribute, in early graft failure in patients, a coronary artery bypass grafting (CABG). To investigate the possible association of ultimate luminal occlusion to VEGFs and CAVs expression, a functional analysis (based on the molecular biology, bioinformatics, histology, and clinical studies) was performed. Twenty-four hundred and sixty-eight CABG patients diagnosed with multivessel stable coronary artery disease (CAD) were enrolled into prospective study and assigned to two subgroups: double- and triple-vessel CAD subjects. Distal parts of all the harvested saphenous vein (SV) and internal thoracic artery (ITA) segments were used for further tests. ITA graft failure did not differ between double-vessel and triple-vessel CAD patients. The number of SV occlusions was significantly higher in triple-vessel CAD subjects. The microarray analysis performed on SV and ITA samples obtained exclusively from triple-vessel CAD patients who developed early graft occlusion revealed 383 genes with increased and 301 genes with decreased expression in ITA samples as compared to SV grafts. This was followed by functional analysis of ‘blood vessel development’ group of genes. Average VEGF-C expression in ITA grafts was higher than in corresponding SV grafts; FLT4 expression was significantly higher in SV than in ITA transplants. VEGFR-3 and CAV3 expression demonstrated immunohistochemically in SMCs of the tunica media of SV grafts predicted their early restenosis in triple-vessel CAD patients. CAV2 protein expression in SMCs of ITA grafts indicated the risk of early graft failure both in double-vessel and triple-vessel CAD subjects.